2011
DOI: 10.1007/s10450-011-9359-x
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of heavy metals on adapted Aspergillus foetidus

Abstract: The development of the organisms extracellular and intracellular mechanisms for the uptake of heavy metals were conducted by using the natural detoxification strategies of the organism to toxicity. Aspergillus foetidus was used as a test case organism to examine these processes. Aspergillus foetidus was adapted to multi-metals (Al, Co, Cr, Cu, Fe, Mg, Mn, Ni and Zn) by a sequential method for tolerance development. The detoxification strategies of A. foetidus occurred by two mechanisms. The first mechanism is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Ge et al . () suggested that the adaptation of fungi towards heavy metals will lead to modification of the hyphae cell surface believed to be involved in intracellular detoxification of heavy metals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ge et al . () suggested that the adaptation of fungi towards heavy metals will lead to modification of the hyphae cell surface believed to be involved in intracellular detoxification of heavy metals.…”
Section: Resultsmentioning
confidence: 99%
“…Helander (1995) found a higher tolerance towards Ni and Cu of an endophytic fungal strain, Hormonema sp., that was isolated from a plant taken near the pollution source (a factory in Harjavalta) compared to isolates obtained from the same plant species but taken 8 km away from the factory, where the pollution level is lower. Ge et al (2011) suggested that the adaptation of fungi towards heavy metals will lead to modification of Table 2 Biosorption capacity (mg g À1 ) of the live and dead biomass of the isolated fungi on heavy metal copper biosorption…”
Section: Biosorption Of Cu By Live and Dead Fungal Biomassmentioning
confidence: 99%
“…The effects of contact time (1-7 days) [13], pH (4, 5, and 6) [17], and initial Cd concentrations (25,50, and 100 ppm) [16] on removal capacity of active mycelia were determined respectively. Time course experiments, were conducted in 250 mL Erlenmeyer flasks with a working PDB volume of 100 mL contaminated with 100 ppm Cd concentration at pH 6.…”
Section: Bioaccumulation Tests By Growing Fungusmentioning
confidence: 99%
“…Thiols are a well-known for metal chelation and detoxification. Some important members of the thiol family are capable of binding heavy metal ions to thiol-containing compounds such as GSH and sequestering these metal-thiol complexes into sub-cellular compartments of vacuoles (Schmoger et al, 2000 andGe et al, 2011). …”
Section: Effect Of Cu(ii) On Thiol Content Of a Awamorimentioning
confidence: 99%
“…One of them is the production of extracellular metabolites (e.g. citrate, oxalate) that is capable of adsorbing and precipitating the metal ions on the cell surface (Ge et al, 2011). …”
Section: Oxalic Acid Secretionmentioning
confidence: 99%